'Invested' partnerships as key to high quality apprenticeship programmes as evidenced in on and off the job training. Issue 3 (3rd April 2023) - Brockmann, Michaela; Smith, Rob
ABSTRACT: In England, a new model of apprenticeship was initiated in whose stated intention was to 'put employers in the driving seat'. Regulation of the new model was focused on the mandatory 20% of apprentices' work time allocated to off-the-job training offered by colleges and other training providers. Based on case studies of employers and training providers across a range of industry sectors, this paper brings together data from two projects researching the on-the-job and off-the-job training elements of the new model. Three contrasting modes of apprenticeship emerged: developing apprentices to become experts in an industry-wide community of practice; apprenticeship as staff development; and apprenticeship as income stream. These resulted from different forms of employer-provider collaboration, enabled through a marketized landscape of training providers, and flexibility in regulations that requires very little of employers. Utilising Fuller and Unwin's work on expansive and restrictive environments, we found that that the new model supports a range of apprenticeships some being excellent but also others that are not worthy of the me. The paper concludes that quality apprenticeships tended to be in traditional industries and relied on strong partnerships between employers and training providers that worked against the grain of competitive market relations.